Tsongkhapa Losang Drakpa, Great Treatise on the Stages of Mantra: Chapters XI–XII (The Creation Stage). Annotated translation by Thomas Freeman Yarnall - Zrenner, Michael (Religions of South Asia, 2014)
Tsongkhapa Losang Drakpa, Great Treatise on the Stages of Mantra: Chapters XI–XII (The Creation Stage). Annotated translation by Thomas Freeman Yarnall. New York: American Institute for Buddhist Studies/Columbia University Press, 2013. xxiii + 381 pp. £38.50. ISBN 978-1-935011-01-9 (hardback).